2023
DOI: 10.1001/jamaophthalmol.2023.0267
|View full text |Cite
|
Sign up to set email alerts
|

Financial Disclosures Reported by Industry Among Authors of the American Academy of Ophthalmology Clinical Practice Guidelines

Abstract: ImportanceRecommendations of clinical guidelines affect physicians’ care delivery. Potential bias and undeclared conflicts of interests (COIs) among guideline authors can impact clinical practice decisions.ObjectiveTo assess financial disclosures reported by physician authors of the American Academy of Ophthalmology (AAO) Practice Pattern Guidelines compared with those reported by industry to evaluate the disclosures’ accuracy.Design, Setting, and ParticipantsIn this cross-sectional study, all clinical guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…So it would appear disappointing that, as Nyugen et al report in JAMA Ophthalmology , based on a comparison with data published in the CMS Open Payments website, a large percentage of the authors of 24 American Academy of Ophthalmology (AAO) clinical practice guidelines published between 2016 and 2020 failed to disclose their financial interests accurately or at all in connection with guideline development. The study authors point out that practice guidelines (AAO terms them preferred practice patterns ) can directly impact patient care, making the importance of transparency on the part of guideline authors all the more critical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So it would appear disappointing that, as Nyugen et al report in JAMA Ophthalmology , based on a comparison with data published in the CMS Open Payments website, a large percentage of the authors of 24 American Academy of Ophthalmology (AAO) clinical practice guidelines published between 2016 and 2020 failed to disclose their financial interests accurately or at all in connection with guideline development. The study authors point out that practice guidelines (AAO terms them preferred practice patterns ) can directly impact patient care, making the importance of transparency on the part of guideline authors all the more critical.…”
mentioning
confidence: 99%
“…The Open Payments website is the most easily accessible source of data on physicians’ payments from medical device and drug manufacturers. As Nyugen et al observe, Open Payments has limitations. However, given its wide scope and easy accessibility, those for whom disclosure is critical have little excuse for failing to consult it, whether as authors required to disclose their interests, or as publishers and trusted authorities, such as specialty societies, that need to carry out and enforce disclosure standards.…”
mentioning
confidence: 99%
“…To the Editor We would like to commend Nguyen et al on their excellent study investigating the financial disclosure practices among male and female physicians. The authors use rigorous methodology in their acquisition, analysis, and interpretation of their data.…”
mentioning
confidence: 99%
“…Therefore, we encourage the researchers to use gender identification that is self-reported, which can be found in reputable databases, such as the NPI. Furthermore, other available variables in the NPI data set, such as terminal degree (MD or DO) or current geographic location, could have been used as covariables in the study to account for variability in payments that results from factors other than gender and strengthen the validity of the reported findings. Of note, additional data sets provided by the federal government, such as the National Downloadable File data set, can be linked to the NPI data set to include additional covariables, such as year of medical school graduation.…”
mentioning
confidence: 99%
“…Despite its limitations (gender not considered as a spectrum and not self-reported genders), Gender API is widely used in research due to its high accuracy . In our study, Gender API determined the gender of 188 author names: 83 were assigned as women (44.1%) and 105 were assigned as men (55.9%) . To follow the recommendations made by Tinsley et al, we manually reviewed the self-reported gender of authors on the National Provider Index (NPI).…”
mentioning
confidence: 99%